Improvement of Populus Deltoides Bartr. Ex Marsh. in India - Provenance Variation and Intraspecific Breeding - Singh, N. B.; Kumar, Dinesh; Gupta, Rajesh K.; Kumar, Pradeep; Singh, Kadam (Indian Forester, 2013)
A study was made to compare the 1Â½ years performance of seedlings belonging to Eastern Gulf (EG), East central (EC) and Southeast Atlantic (SA) sub-regions of South-eastern USA. The collar diameters were in the order of SA>EG>EC. Variation among stands was significant for collar diameter and number of branches per metre of stem length. About 14700 seedlings belonging to 66 control-pollinated families and 5000 seedlings belonging to 20 open-pollinated families have been produced. Selection and cloning of promising genotypes was done. Testing of clones is in progress.